2022
DOI: 10.3390/biomedicines10082025
|View full text |Cite
|
Sign up to set email alerts
|

Hemin Ameliorates the Inflammatory Activity in the Inflammatory Bowel Disease: A Non-Clinical Study in Rodents

Abstract: Background: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract. Currently, there is no cure, and pharmacological treatment aims to induce and maintain remission in patients, so it is essential to investigate new possible treatments. Hemin is a heme-oxygenase inducer which can confer anti-inflammatory, cytoprotective, and antiapoptotic effects; therefore, it can be considered an asset for different gastrointestinal pathologies, namely for IBD. Aim: This experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The improvement of H in the weight could be attributed to the decrement in MDA content which increased by CuO NPs or to the antioxidant property of H (Ali et al, 2019). Silva et al (2022) disagreed with these findings and reported that H did not show any apparent impact on the animals' body weight.…”
Section: Discussionmentioning
confidence: 88%
“…The improvement of H in the weight could be attributed to the decrement in MDA content which increased by CuO NPs or to the antioxidant property of H (Ali et al, 2019). Silva et al (2022) disagreed with these findings and reported that H did not show any apparent impact on the animals' body weight.…”
Section: Discussionmentioning
confidence: 88%
“…RenderX pharmacological approach to treatment of inflammatory-related diseases, considering its efficacy and safety over the short or long term. Indeed, several nonclinical studies have already demonstrated that hemin has a significant anti-inflammatory effect in different contexts, such as in inflammatory bowel disease [2,6,16,17], kidney dysfunction [18][19][20], sepsis [21][22][23], arthritis [24,25], pancreatitis [26][27][28], cardiac infarction [29], and airway inflammation [30][31][32].…”
Section: Xsl • Fomentioning
confidence: 99%
“…However, the administration of hemin can also induce the expression of the heme oxygenase (HO) enzyme, which is known as a rate-limiting enzyme for heme catabolism and is responsible for the production of biliverdin, free iron, and carbon monoxide [2,6,7]. Currently, there are 3 identified HO isoenzymes in mammals: HO-1, HO-2, and HO-3 [2,6]. HO-1 is expressed as a response to tissue damage and demonstrates cytoprotective action capable of inhibiting the inflammatory response and oxidative stress [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Hemin was deemed safe in terms of extraintestinal manifestations, showing no adverse effects on the kidneys or liver. As a result, the authors concluded that Hemin treatment could represent a novel pharmacological approach to managing IBD [ 6 ]. Kim and colleagues evaluated the effectiveness of inhibiting Sirtuin 7 (SIRT7) in a colitis mouse model.…”
mentioning
confidence: 99%